Which Training Works? Evaluating the Effectiveness of Teacher Training Programs on Classroom Disorder - Putra, Eka (Journal of Interdisciplinary Studies in Education, 2026)
This study examines the effectiveness of thirteen different training programs in mitigating widespread classroom disorder and evaluates school policy acceptance toward three distinct student groups. Specifically, it identifies which training programs have a significant impact on reducing or preventing classroom disruptions. Using ordinal logistic regression, the analysis draws on a dataset of 2,762 responses from the 2017–18 School Survey on Crime and Safety (SSOCS), encompassing schools across urban, suburban, town, and rural settings in the United States. Findings indicate that only four training programs—classroom management, security procedures training, mental health intervention training, and positive behavior intervention—significantly enhance the likelihood of reducing classroom disorder. Additionally, among school policies examined, only those promoting cultural diversity, such as cultural awareness clubs, demonstrate a meaningful positive effect on mitigating widespread classroom disruptions. The study identifies four key training-based competencies essential for teachers: classroom management, security procedures, mental health intervention, and positive behavior support.